Pengaruh Gadget Terhadap Menurunnya Literasi Siswa Madrasah Aliyah Al-Ghozaliyah Jogoroto Jombang - Imam Mashudi Latif; Adibah Adibah; Riska Maulana (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
ABSTRACT This research was conducted at Madrasah Aliyah Al-Ghozaliyah Jogoroto Jombang with the aim of determining the effect of gadgets on student literacy. This type of research is field research using a quantitative approach. Data collection techniques include observation, interviews, questionnaires, and document analysis. Simple linear regression analysis was used for data analysis. The results showed that gadgets influence student literacy. Based on reliability analysis, the alpha value for each variable was 0.772 for the gadget variable (X), while the alpha value for the literacy variable (Y) was 0.849. Therefore, it can be concluded that the hypothesis that gadget use influences student literacy at Madrasah Aliyah Aliyah Al-Ghozaliyah Jogoroto Jombang is acceptable. Keywords: gadgets, literacy, students